XIX зууны төгсгөл XX зууны эхэн үеийн монгол уран зохиолын зарим бичил төрөл зүйлийн асуудалд - Г., Нарантунгалаг (Mongolian Studies, 2023)
In previous studies, ‘Word’ and ’Dialogue’are considered to be either same genre or dissimilar one that have twomeanings within fairytale-stories. According to our study, these two genres are relatively independent of each other. During the process of development, ‘Fairytale’ shifted to ’Fairytale-stories’ and ‘Fairytale-stories’ to ‘Narratives ’ whereas ‘Word’ to ‘Dialogue ’ which area micro-genre of novels that transferred to modem drama.